Tax revenue instability and tax revenue in developed and developing countries - Sèna Kimm Gnangnon (Applied Economic Analysis, 2022)
Purpose – This paper aims to explore the effect of non-resource tax revenue instability on non-resource tax revenue in developed and developing countries. Design/methodology/approach – The analysis has used an unbalanced panel data set of 146 countries over the period 1981–2016, as well as the two-step system generalized methods of moment approach. Findings – The empirical analysis has suggested that non-resource tax revenue instability influences negatively non-resource tax revenue share of gross domestic product. The magnitude of this negative effect is higher in less developed countries than in relatively advanced countries. This negative effect materializes through public expenditure instability: non-resource tax revenue instability exerts a higher effect on non-resource tax revenue share as the degree of public expenditure instability increases. Finally, non-resource tax revenue instability exerts a higher negative effect on non-resource tax revenue share as economic growth volatility rises, inflation volatility increases and terms of trade instability increases. Research limitations/implications – The main policy implication of this analysis is that policies that help ensure the stability of non-resource tax revenue also contribute to improving countries’ non-resource tax revenue share. For example, governments’ measures that help cope with or prevent the severe adverse effects of shocks on economies (shocks that could translate into higher tax revenue instability) would ultimately help enhance countries’ tax revenue performance. Practical implications – The severity of the current COVID-19 pandemic shock (which is a supply and demand shock) and the macroeconomic uncertainty that it has generated – inter alia, in terms of economic growth instability, terms of trade instability, inflation volatility and public expenditure instability – are likely to result in severe tax revenue losses. Governments in both developed and developing countries would surely learn from the management of this crisis so as to prepare for possible future economic, financial and health crises with a view to dampening their adverse macroeconomic effects, including here their negative tax revenue effects. Originality/value – To the best of the author’s knowledge, this topic is being addressed in the empirical literature for the first time.